Nutrition knowledge and practice of midwives in Botswana - Anastacia Masesane; Thembekile Dhlamini; Maria Nnyepi; Xikombiso Mbhenyane (AOSIS, 2024)
Background: The roles and responsibilities of midwives include providing adequate nutrition assessment, nutrition and health education, counselling, and support to pregnant women. Aim: This study aims to assess midwives' nutrition knowledge and to what extent they integrate maternal nutrition in services provided at health facilities. Setting: This study included hospitals and clinics within the three selected districts in Botswana. Methods: A cross-sectional study design with an analytical component was employed. Direct observation through a checklist and a structured interviewer-administered questionnaire were used. Data were analysed using SPSS IBM version 26. Results: A sample of 102 midwives participated, resulting in a response rate of 82%. Most of the participants were females (89.2%). Maternal nutrition knowledge was found to be variable but decreased with midwives' age. A statistically significant correlation coefficient of p  0.005 at r = -0.278 was observed between maternal nutrition knowledge and age. Similarly, there was a statistically significant negative correlation between maternal nutrition knowledge, practices and maternal nutrition course attended using Pearson correlation (r = -0.217 p  0.028). Conclusion: Midwives had adequate to variable but declining maternal nutrition knowledge and practices with age. There is a need to provide midwives with refresher courses, as their nutrition knowledge and practices were related with courses attended. Contribution: The study contributes to provide the literature concerning nutrition knowledge and practices of midwives. The results will assist in addressing the gaps encountered and lead to the improvement of maternal nutrition and pregnancy outcomes.